Metabolic syndrome: Differences for Asian Americans is in their percentage of body fat - Patricia Alpert; Diane L. Thomason (JMIR Publications, 2016)
Asian Americans are not frequently thought of as being obese or overweight yet some of the Asian American subgroups have a disproportionate risk for cardiovascular disease and type 2 diabetes mellitus. Although the standardized body mass index (BMI) assessment is an adequate tool for reporting secular prevalence trends for overweight/obesity across populations, it falls short in accuracy when assessing Asian Americans. In recent years more has been written about the re-evaluation of BMI cut points for normal weight, overweight, or obese Asian Americans. Additionally, the waist circumference norm was modified to indicate a smaller waist size is a risk for metabolic syndrome. The purpose of this paper is to provide an overview of the research literature on BMI and percentage of body fat as it relates to health risk for metabolic syndrome for Asian American subgroups. Three databases were used to identify articles for this review: Google Scholar, CINHAL, and PubMed. Seven hundred twenty-six articles were initially identified as meeting the criteria; 690 articles were eliminated after a review of the article titles revealed the content did not meet the focus of this review. Of the remaining articles, 19 were eliminated after a review of the abstracts indicated they were meta-analyses, review articles, or case studies. The remaining 18 articles were included in this review. Three common themes emerged. (1) The differences in BMI and body fat percentage are evident between Asian Americans and other ethnic groups. (2) Differences in the percentage of body fat exist between Asian American subgroups, and between Asian Americans and Asian immigrants. (3) There are differences in disease development end points when comparing Asian American subgroups and Asian immigrant subgroups. There are differences in body fat distribution and body fat percentages as well as BMI compared to other ethnic groups for metabolic syndrome. There are also differences between Asian immigrant/Asian American subgroups whereby some are more susceptible to diabetes and cardiovascular disease. Research is necessary to determine if these differences have an underlying genetic predisposition. Additionally, researchers need to oversample Asian immigrant/Asian American participants in comparison studies and need to identify each subgroup in their research rather than aggregating Asian immigrants/Asian Americans by geographical origin or as one common group designated as a generic group of "Asians."